Advancing health equity through partnerships of state Medicaid agencies, Medicaid managed care organizations, and health care delivery organizations - Anna L. Thorndike; Lauren Peterson; Sivan Spitzer; Shilpa Patel; Anne Smithey; Jennifer E. Moore; Jennifer E. Moore; Scott C Cook; Marshall H. Chin (Frontiers in Public Health, 2023)
BackgroundReducing health inequities in marginalized populations, including people with Medicaid insurance, requires care transformation to address medical and social needs that is supported and incentivized by tailored payment methods. Collaboration across health care stakeholders is essential to overcome health system fragmentation and implement sustainable reform in the United States (U.S.). This paper explores how multi-stakeholder teams operationalized the Roadmap to Advance Health Equity model during early stages of their journey to (a) build cultures of equity and (b) integrate health equity into care transformation and payment reform initiatives.MethodsAdvancing Health Equity: Leading Care, Payment, and Systems Transformation is a national program in the U.S. funded by the Robert Wood Johnson Foundation that brings together multi-stakeholder teams to design and implement initiatives to advance health equity. Each team consisted of representatives from state Medicaid agencies, Medicaid managed care organizations, and health care delivery organizations in seven U.S. states. Between June and September 2021, semi-structured interviews were conducted with representatives (n = 23) from all seven teams about experiences implementing the Roadmap to Advance Health Equity model with technical assistance from Advancing Health Equity.ResultsFacilitators of building cultures of equity included (1) build upon preexisting intra-organizational cultures of equity, (2) recruit and promote diverse staff and build an inclusive culture, and (3) train staff on health equity and anti-racism. Teams faced challenges building inter-organizational cultures of equity. Facilitators of identifying a health equity focus area and its root causes included (1) use data to identify a health equity focus and (2) overcome stakeholder assumptions about inequities. Facilitators of implementing care transformation and payment reform included (1) partner with Medicaid members and individual providers and (2) support and incentivize equitable care and outcomes with payment. Facilitators of sustainability planning included (1) identify evidence of improved health equity focus and (2) maintain relationships among stakeholders. Teams faced challenges determining the role of the state Medicaid agency.ConclusionsMulti-stakeholder teams shared practical strategies for implementing the Roadmap to Advance Health Equity that can inform future efforts to build intra- and inter-organizational cultures of equity and integrate health equity into care delivery and payment systems.